Guess and determine attack on E0algorithm - Ying-jie ZHAN; Lin DING; Jie GUAN (Tongxin xuebao)
A guess and determine attack on E0was presented,the stream cipher that was used in the short-range wireless technology Bluetooth.In the attack,an ingenious assumption by linear approximation to diminish the number of values that have to be guessed was made.Futher more,a test equation to reduce the number of the guessed candidates was used.The guess and determine attack on E0with time complexity of O(276)required about 988 keystream bit.Compared with long keystream attacks,short keystream attacks were more threatening to E0cipher which require less than 2 745 bit.This attack which belongs to short keystream attack was the fastest state recovery attack on E0so far compared with any other existed short keystream attacks.